Cultural differences in the perception of credible online reviews – The influence of presentation format - Brand, Benedikt M.; Reith, Riccardo (Decision Support Systems, 2022)
As recently several authors postulated the need to examine the credibility of online reviews (ORs) in an intercultural context, we investigate this issue by building upon different theoretical frameworks and upon insights gained from an eye-tracking pre-study. Herein, the study is the first to explore ORs' credibility in an intercultural comparison. Moreover, no other study has shed light on the effect of OR's presentation format by incorporating cross-national perspectives yet. Applying a (2 × 2) between subjects experiment design, the results indicate that video reviews are able to only slightly increase arguments' quality effect on review credibility compared to textual reviews. However, differences occurred based on nationality, gender, and online shopping frequency. Furthermore, intercultural differences were detected between the effects of review consistency on review credibility, of review rating on review credibility, and of review credibility on purchase intention. •First study to investigate review credibility interculturally.•Eye-tracking pre-study as foundation for a 2 (text vs. video) x 2 (two high-involvement products) between subjects experimental design.•First study to investigate the effect of varying presentation formats interculturally (Chinese and Germans).•Video reviews can increase the effect of the arguments raised on review credibility dependent on nationality, gender, online shopping frequency.